A case of upper gingiva carcinoma with chronic graft‐versus‐host disease after allogenic bone marrow transplantation. (24th July 2015) - Tsushima, F; Sakurai, J; Harada, H
Abstract Oral squamous cell carcinoma (OSCC) is one of the most common solid tumours occurring after haematopoietic stem cell transplantation (HSCT), especially in patients with chronic graft‐versus‐host‐disease (cGVHD). We describe a case of OSCC that developed in a 51‐year‐old male 22 years after he had received allogeneic HSCT from his human leukocyte antigen‐identical sister as a treatment for acute myelocytic leukaemia. The patient had presented with multiple white patchy lesions on the palatal gingiva and mucosa 16 years after HSCT; these lesions were consistent with the clinical features of cGVHD. Six years later, oral examination and biopsy revealed upper gingival squamous cell carcinoma (SCC) in areas of cGVHD, and he underwent tumour excision. Follow‐up examination at 2 years and 4 months after the operation revealed no evidence of recurrence of local SCC or metastasis of the cervical lymph node. The current case highlights the susceptibility of patients with cGVHD to the development of OSCC even two decades after HSCT. Therefore, we recommend careful long‐term follow‐up of the oral cavity for patients with cGVHD.